The effect of Perceived Environmental Uncertainty, Management Control Systems and Strategy on Performance - Huusko, Jonna (My University, 2008)
Contingency theory has been widely used in management accounting research, particularly in study of management control systems. The effectiveness and increased performance of a company have been attempted to explain by investigating environment, management control systems and strategy. The aim of this research is to examine the affect of perceived environmental uncertainty on strategy, management control systems and performance in profit-making service and manufacturing organisations. Most of the contingency- based studies have been conducted on manufacturing and service industry. Management control systems in service organisations have been examined however, studies have been mainly case studies and the organisations have been non-profit oriented. This study attempts to investigate and compare the contingency relations in profit-oriented service and manufacturing companies. The results are conducted from 66 responses (response rate 13%). The findings of the study suggest that industry does not make a difference in the contingency relations. The results confirmed the existence of some contingency relations. Organisations which have adopted prospector strategy perceive higher environmental uncertainty. Companies which perceive high environmental uncertainty are likely to use non-financial management control systems. Additionally, there is a positive relationship between non-financial control systems and performance. Keywords: Contingency theory, performance, service industry
Keywords: Contingency theory; performance; service industry; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|